Dealing with Excessive Off-label Drug Use: Liability vs. Patent Prolongation - Stefan Felder; Anja Olbrich (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2009)
The US and the EU recently introduced regulation to curb the extent of risky off-label drug use. It offers manufacturers a prolongation of patent protection or exclusivity if they invest in pediatric clinical tests. This paper shows that a reinforcement of physician liability for off-label use may be the preferred instrument for achieving dynamic efficiency. The liability threat reduces the demand for off-label use, giving manufacturers an appropriate incentive to invest in extended approval. By contrast, patent prolongation does not affect physicians' prescription decisions and increases the likelihood of investments in cases where the induced additional benefit falls short of testing costs.
Keywords: I11; K13; 330; Off-label use; patent protection; exclusivity; liability; Pharmazeutisches Produkt; Gesundheitsrisiko; Arzneimittelrecht; Haftung; Ärzte; Patentrecht; Theorie